PENINGKATAN HASIL BELAJAR MENGURAIKAN KOSAKATA BERBAGAI JENIS BENDA MELALUI MODEL SCRAMBLE DENGAN PENGUATAN KARAKTER RASA INGIN TAHU PADA SISWA KELAS I SDN I KEDUNGLURAH KABUPATEN TRENGGALEK - Lilinggarwati, Lilinggarwati; Sutansi, Sutansi; Murti, Tri Murti (Wahana Sekolah Dasar, 2023)
This study aims to describe the increase in learning outcomes material describing vocabulary through the application of the scramble model by strengthening the character of curiosity in grade 1 students of SDN 1 Kedunglurah, Trenggalek Regency. This study uses a qualitative approach using the type of Classroom Action Research. The results of observations of the average value of student learning outcomes at the pre-action stage is 52.85 with a classical learning completeness of 40.74%. In the first cycle the average value of student learning outcomes increased to 66.85 with a mastery of classical learning by 55.55% and the value of the percentage of teacher activity and student activity by 85%. In cycle II the average value of student learning outcomes increased again to 78.96 with a classical learning completeness of 90.74% and the value of the percentage of teacher activity and student activity by 100%. Based on the results of the research cycle I and cycle II show that the scramble learning model with the strengthening of curiosity character can improve student learning outcomes material describing vocabulary.